PENGARUH KEGIATAN MEMBATIK DENGAN TEKNIK ECOPRINT TERHADAP PERKEMBANGAN KREATIVITAS ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK (TK) SAHNA PERDHANA - Miftahul Jannah; Humaidah Br. Hasibuan; Raisah Armayanti Nasution (CV. ADIBA AISHA AMIRA, 2024)
This study aims to see the effect of batik activities with ecoprint techniques on the development of creativity of children aged 5-6 years at Sahna Perdahana Kindergarten. This type of research is quantitative research using experimental methods. The design used is Pre-Experimental Design with the form of One Group Pretest Posttest Design. The population in this study was 14 children. The sampling technique in this study used a non-probability sampling technique, namely saturated samples or what is often called total sampling. The instrument used was an observation sheet. The data analysis techniques used were normality test, homogeneity test, and hypothesis test. The results of the study average Pre Test 47.14 after Post Test treatment with an average value of 70. The results of the hypothesis test obtained tcount> ttable, namely 22.434> 2.179 at a significant level of α = 0.05 Thus, the hypothesis H0 is rejected and Ha is accepted so that it is stated that there is a significant effect of batik activities with ecoprint techniques on the development of creativity of children aged 5-6 years at Sahna Perdhana Kindergarten.